Effect of low intensity photobiomodulation associated with norbixin-based poly (hydroxybutyrate) membrane on post-tenotomy tendon repair. In vivo study - Nascimento,Lízia Daniela e Silva (2020)
Abstract Purpose: To evaluate the in vivo response of photobiomodulation therapy associated with norbixin-based poly(hydroxybutyrate) membrane (PHB) in tenotomized calcaneal tendon. Methods: Thirty rats were randomly allocated to six groups (n=5 each): LED groups (L1, L2 and L3) and membrane + LED groups (ML1, ML2 and ML3). The right calcaneal tendons of all animals were sectioned transversely and were irradiated with LED daily, one hour after surgery every 24 hours, until the day of euthanasia. At the end of the experiments the tendons were removed for histological analysis. Results: The histological analysis showed a significant reduction in inflammatory cells in the ML1, ML2 and ML3 groups (p=0.0056, p=0.0018 and p<0.0001, respectively) compared to those in the LED group. There was greater proliferation of fibroblasts in the ML1 (p<0.0001) and L3 (p<0.0001) groups. A higher concentration of type I collagen was also observed in the ML1 group (p=0.0043) replacing type III collagen. Conclusion: Photobiomodulation in association with norbixin-based PHB membrane led to control of the inflammatory process. However, it did not favor fibroblast proliferation and did not optimize type I collagen formation in the expected stage of the repair process.